Associations between serum amyloid A, interleukin‐6, and COVID‐19: A cross‐sectional study. Issue 10 (28th August 2020) - Liu, Qian; Dai, Yaping; Feng, Meimei; Wang, Xu; Liang, Wei; Yang, Fumeng
Abstract: Background: Serum amyloid A (SAA), interleukin‐6 (IL‐6) and neutrophil‐to‐lymphocyte ratio (NLR) play critical roles in inflammation and are used in clinical laboratories as indicators of inflammation‐related diseases. We aimed to provide potential laboratory basis for auxiliary distinguishing coronavirus disease (COVID‐19) by monitoring above indicators. Methods: A total of 84 patients with confirmed COVID‐19 were enrolled in the study. Baseline characteristics and laboratory results were collected and analyzed. Receiver operating characteristic (ROC) curve analysis was used to combined detection of SAA and IL‐6 in patients with COVID‐19, and independent risk factors for severity of COVID‐19 were assessed by using binary logistic regression. Results: The main clinical symptoms of patients with COVID‐19 were fever (98.8%), fatigue (61.9%), and dry cough (58.3%). SAA, IL‐6, and NLR were significantly higher in patients with COVID‐19 (all P < .001), and compared with nonsevere patients, three indicators of severe patients were significantly elevated. Besides, combined detection of SAA and IL‐6 better separates healthy people from patients with COVID‐19 than detection of SAA or IL‐6 alone. In addition, elevated SAA, IL‐6, and NLR can be used as independent variables for predicting the severity of patients with COVID‐19. Conclusion: Serum amyloid A and IL‐6 could be used as addition parameters to helping the distinguish of patients with COVID‐19 from healthy people, and can provide potential basis for separating patients with nonsevere and severe clinical signs. Abstract : Comparison of laboratory indicators among patients with COVID‐19